19F-nuclear magnetic resonance study of glycerolipid fatty acyl chain order in Acholeplasma laidlawii B membranes. - McDonough, B. (Yale Journal of Biology and Medicine, 1983)
The technique of 19F-nuclear magnetic resonance (19F-NMR) spectroscopy offers a number of advantages for studies of lipid fatty acyl chain orientation and dynamics in biomembranes. However, the geminal difluoromethylene fatty acid probes usually employed in such studies appreciably perturb the organization of lipid bilayers. We have thus synthesized a series of specifically monofluorinated palmitic acids and carried out biophysical, biochemical, and physiological studies establishing their suitability as relatively non-perturbing probes of lipid hydrocarbon chain organization. These 19F-NMR probes were then used to determine the fatty acyl chain order profiles of Acholeplasma laidlawii B membranes highly enriched in a variety of different exogenous fatty acids, particularly those containing a methyl branch or a trans-double bond.